Pengembangan Kurikulum Masyarakat, Pendidikan dan Sekolah - Gusti Rantio; Hery Noer Aly (Departement of Mathematics Education, 2023)
The issues raised in this study are Community, Education and School Curriculum Development. In this study, the authors used the library research method, namely in writing articles, the authors used books as their data source. Library research which is commonly called library research is carried out by examining written sources. The nature of this research is descriptive-analytic, discussed clearly, sequentially, and directed. The research subject in this article is from secondary data. Secondary sources, namely data obtained not from main books but from these books contain supporting data. Usually these books are the result of a review of the main book. The secondary sources used in this article come from books that discuss matters related to the curriculum development process. The purpose of this research is to discuss the relationship between education, society, school, and curriculum. Initially, schools were established to pass on the cultural content of society to the younger generation so that they master knowledge, skills and values ​​that help them live well in their society. That is, by mastering and adhering to the cultural values ​​of the people, the younger generation of a society can live successfully as the older generation has experienced for themselves. In this context, the function of education is to transfer culture as it is to the younger generation.